Novel Discoveries in Immune Dysregulation in Inborn Errors of Immunity - Ren, Anwen; Yin, Wei; Miller, Heather; Westerberg, Lisa S.; Candotti, Fabio; Park, Chan-Sik; Lee, Pamela; Gong, Quan; Chen, Yan; Liu, Chaohong (Frontiers in Immunology, 2021)
With the expansion of our knowledge on inborn errors of immunity (IEI), it gradually becomes clear that immune dysregulation plays an important part. In some cases, autoimmunity, hyperinflammation and lymphoproliferation are far more serious than infections. Thus, immune dysregulation has become significant in disease monitoring and treatment. In recent years, the wide application of whole-exome sequencing/whole-genome sequencing has tremendously promoted the discovery and further studies of new IEI. The number of discovered IEI is growing rapidly, followed by numerous studies of their pathogenesis and therapy. In this review, we focus on primary immune dysregulation diseases, including their genetic mutation, symptoms and current therapeutic methods, and point out the gaps in this field.